Implementation of Asmaul Husna Values through Storying Method in Early Children - Eko Nursalim; Umar Fauzan; Noor Malihah (Budapest International Research and Critics University, 2022)
Learning at an early age requires teaching methods adapted to the child's growth period. The purpose of this study was to find out the inculcation of the values of Asmaul Husna through the storytelling method in early childhood, the obstacles faced, and the solutions. This research method uses a classroom action research model. Collecting data utilizing observation and evaluation of each cycle, interviews, and equipped with a literature review. The result of this research that has been done is that the storytelling method can increase the cultivation of Asmaul Husna's values. Obstacles during the study include teacher preparation that was still lacking in teaching, foreign intelligence of children, and the lack of teaching aids and learning resources. The solution is to get used to the professionalism of teachers in teaching, the roles and responsibilities of parents to educate their children at home continuously, and the seriousness of PAUD institutions in completing learning facilities and infrastructure.